Durability performances of ferronickel slag aggregate and seawater concrete - Nevy Sandra; Muhammad Akbar Caronge; Jati Sunaryati; Keiyu Kawaai; Willick Nsama; Yaumal Arbi; Ari Syaiful Rahman Arifin (Universitas Negeri Padang, 2025)
The rising demand for concrete in the building sector has resulted in the exhaustion of natural sand and freshwater supplies, leading to the pursuit of sustainable substitutes. Coastal areas have plentiful ferronickel slag (SL) and seawater (SW), which can be used to manufacture concrete. Nevertheless, the possibility of corrosion to steel reinforcement raises concerns that require further research. This investigation examines the mechanical and durability performance of concrete that incorporates SL as a partial replacement for fine aggregate and SW as a mixing component. The objective is to optimize SL content to improve compressive strength, resistance to chloride ions, and overall durability. Experimental results show that replacing 25% of the aggregate with SL yields the best combination of workability, strength, and durability, significantly enhancing compressive strength, decreasing porosity, and lessening chloride ion penetration, as evidenced by the Rapid Chloride Penetration Test (RCPT). Although seawater promotes early-age hydration and strength development, its extended use slightly diminishes compressive strength due to salt-induced micro-cracking. However, SL counters these effects, making SW–SL mixture a feasible and sustainable option for concrete production in coastal and resource-limited areas. A significant relationship between RCPT and compressive strength underscores the important role of SL in densifying the matrix and improving impermeability. The concrete mixture with 25% SL exhibits the lowest abrasion weight loss at 28 and 120 days, showing improved durability. This study highlights the potential of using SL and seawater to create eco-friendly and high-performance concrete for harsh environments.